Security Risk Governance: A Critical Component to Managing Security Risk - Allen, Brian; Xu, Mengzhu; Xu, Heli; Wang, Zhuoran; Rakotomavo, Michel; Kmetetz, Andrew; Awojulu, Adegbenro; Poole, Amy; Loyear, Rachelle; Kelly, Timothy; Yuan, Huaijin (Journal of Applied Business and Economics, 2018)
This paper proposes that security risk be managed at the same corporate level and with the same focus as financial risk, regulatory risk, or operational risk. It reviews related corporate governance and risk Journal of Applied Business and Economics Vol. 20(1) 2018 133 management concepts and shows applications into a variety of case studies from real businesses across the traditional risk management footprint. Using the framework of enterprise security risk management, it illustrates how security risk can be managed as any other type of risk and suggests some oversight and governance models for the security risks that could impact and damage business assets and functions.